Establishing a culture of environmental sustainbility in a university : A case study of Boğaziçi University - Teoman, Cahit Berk. (Thesis (M.S.) - Bogazici University. Institute of Environmental Sciences, 2018., 2018)
Higher education is a key area in the sustainable development debate today. More and more universities and colleges around the world are implementing plans and policies to become both environmentally more sustainable on campus level and adapting their education programs to address the rising need for a sustainability-minded generation. Boğaziçi University’s recent efforts in this area are notable and promising. With its alumni network and highly capable students, successful application of a higher education for sustainable development program in all its aspects at the university will have a region spanning impact on sustainable development, as well as providing an example for other universities to follow. Looking at how the university has thus far managed its campus environment and what the current level of education for sustainable development is at the university, within the framework of the campus sustainability scheme UI GreenMetric, and comparing and contrasting them with the results of an awareness and willingnessto-act assessment questionnaire study of the students and alumni would provide key recommendations that could impact the university’s performance significantly. Organization of results into strength, weakness, opportunity and threat areas would map out and guide the university’s efforts towards becoming a leading institute of higer education for sustainable development.
Keywords: Sustainability -- Boğaziçi University.; Higher education -- Boğaziçi University.